Angle of repose [book club bag] - Stegner, Wallace, 1909-1993 (Vintage Books, a division of Random House LLC, 2014)
Stegner's Pulitzer Prize-winning novel is the story of four generations in the life of an American family. A wheelchair-bound retired historian embarks on a monumental quest: to come to know his grandparents, now long dead. The unfolding drama of the story of the American West sets the tone for Stegner's masterpiece.